The comparison of fatty acids, fat-soluble vitamins and cholesterol in the muscle of wild caught, cage and pond reared rainbow trout (Oncorhynchus mykiss W., 1792) - Ural, M. S.; Calta, M.; Parlak, A. E. (Iranian Fisheries Science Research Inst-Ifsri, 2017)
[Abstract Not Available]
Keywords: Oncorhynchus mykiss; Rainbow trout; Fatty acid; Cholesterol; Fat-soluble vitamins